PERAN DINAS PARIWISATA DALAM PEMBANGUNAN INDUSTRI PARIWISATA KOTA BITUNG - Makahinda, Nowzellita; Lengkong, florence Daicy; Tampongangoy, Deysi Livi (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Vision and Mission of the realization of Bitung Bitung City as an international port city, industry, trade,services and tourism environmentally sound and superior in the era of globalization. Furthermore, the missionoutlined in Bitung City Government namely Panca Bina where one of them is the Human Development. Oneprogram in Human Development's mission is determined Bitung City Government and seeks to prepare peoplequalified and highly skilled so that they can compete in the era of globalization while preserving the ethical values,moral and religious norms. But until now the Government's attention to the development of the tourism industryBitung is still very minimal. Less successful development of tourism in the city of Bitung not be separated from theimplementation of policies that are still using the top-down approach is the approach of the party from top to bottom.In the process of implementation of the government's role is very big, in this approach is the assumption that occursdecision makers is a key actor in the success of implementation, while the other parties involved in theimplementation process hampered, so that the decision makers underestimate the strategic initiatives coming fromthe level of bureaucracy Low and subsystems wisdom another. And the non-involvement of the public in policymaking from planning, organizing, implementation and supervision. This research uses qualitative research isresearch that is used to examine the Role of the Government in which the researcher is a key instrument. While datacollection techniques used by researchers is a method that is based on the Interview Interview Guide (interviewguide), documentation and observation. Researchers carrying out research in the Department of Tourism andCulture City of Bitung by using the techniques of data collection guidelines the Department of Tourism.Based on the results of the study: The role of the department of tourism is very important for the developmentof tourism industry strongly support the economy of the town Bitung. And to attract tourists and the infestor engagedin tourism. The role of the tourism department is very influential on the development of the tourism industry in thecity of Bitung. Role of department of tourism is very important because tourism agencies provide recommendationsand input for monitoring the development of the tourism industry. Suggestions for Bitung City Tourism Office is aneed for dissemination to the public of the importance of tourism development. The government should be moreactive in implementing tourism development, both in terms of promoting the attraction - attraction to the local leveland also to the level of long-distance, in order to make it more widely known by the public tourist or foreigncountries about tourism in the city of Bitung. Expected also for the tourism department of government even Bitungfor mutual coordination even coordinated with the central government related to the development of tourism, inorder to resolve the problems or obstacles in the development of tourism.Keyword: Role of the Department, Tourism